Role of information and communication technology (ICT) in facilitating healthy lifestyle among youth in urban poverty - Halili, S.H.; Sulaiman, H. (2015)

(untitled)
The life of youth in urban poverty communities is usually associated with society in poor urban communities. Information and Communications Technology (ICT) is a technology tool to help and facilitate communication and processing besides information delivery through electronic means. One of the elements to help accelerate economic development and social development is the rapid growth of ICT in use. Nevertheless, many problems and challenges are faced by the urban poverty community from the aspect of using leT in creating a healthy lifestyle. Hence, the youth in urban poverty are recommended to take various initiatives in using leT based tools given that leT use is able to change their lifestyle and wellbeing.